Do firms or workers drive the foreign acquisition wage premium? - Marcus Rösch; Michiel Gerritse; Bas Karreman; Frank van Oort; Bart Loog (Tinbergen Institute, 2022)
We decompose the wage premium after foreign acquisitions of Dutch domestic firms into the con- stituent firm- and worker-level premia. Firm-level premia grow up to 3.5%, accounting for the major- ity of the acquisition premium. Worker-level premia by contrast, grow up to 1% and only materialize with delay, as the acquired firms hire workers with higher earnings capacity than domestic firms. Within firms, premia are also higher for workers with a relatively high earnings capacity. Though in- dustry variation and firm size class heterogeneity is considerable, the dominance of firm-level premia suggests that foreign acquisitions change firms beyond a workforce reshuffling.
Keywords: J31; F23; G34; 330; multinational firms; foreign acquisition; wage components; labor mobility; matched employer-employee data; AKM